Determinantes de la estructura de capital de las pymes del subsector de construcción de obras civiles en Bogotá durante el período de 2008 – 2013 - Pineda Cortes, Sandra Milena (Universidad de La Salle. Facultad de Ciencias Económicas y Sociales. Finanzas y Comercio Internacional., 2017)
Considering the development that has been presenting the infrastructure construction and the importance of capital structure for a company and according to the different theoretical approaches that have been developed on the subject, as are the theories of Modigliani and Miller, trade-off and pecking order, arises the objective of this research to identify the determinants of capital structure of SMEs in the subsector of construction of civil works in Bogotá, during the period 2008 to 2013. To find these determinants was used a quantitative methodology, through a panel data model in which financial indicators of liquidity, profitability and operation were included in order to analyze the financial performance of these SMEs during this period and in addition the value that generated these companies, compared to the subsector was evaluated. In conclusion, it was found that most of the financial indicators as the weighted average cost of capital, the size of the company, tangible assets, ROE, among others, are considered determinants of the capital structure of the Bogotá SMEs civil works and which in turn these companies have been showing a positive trend in terms of generation of value compared to the subsector.